Optimizing Digital Pedagogical Competence Through Nano-Learning Models Integrated With Religious Values For Graduatestudents' Professionalism - Arief Rahman Yusuf; Angga Prasetyo; Fauzan Masykur; Bambang Hermanto; Fifi Arisanti; Razali Bin Hassan (Universitas Muhammadiyah Sidenreng Rappang, 2026)
This community empowerment aims to enhance the digital pedagogical competence of cadres through digital propagation content management training to support the national program toward Golden Indonesia two thousand forty-five. This community service activity is conducted at the Darul Hikmah Mosque as the religious center in Ponorogo by utilizing matching funds amounting to ten million rupiahs. The method used is qualitative descriptive, where data analysis techniques are carried out narratively through direct observation, in-depth interviews, and comprehensive documentation of the participants throughout the program. The results of the activity indicate that the implementation of a focused module-based micro-learning model is proven effective in improving the digital literacy and instructional content design skills of the participants. Furthermore, the integration of religious values in this training successfully strengthens the moral foundation of the cadres, ensuring that the developed digital professionalism remains aligned with ethical and spiritual integrity. In conclusion, the synergy between modern learning technology and religious character building significantly strengthens the professional identity of future educators. This model offers a strategic framework for higher education institutions to produce digitally competent graduates who are adaptive to twenty-first-century challenges while remaining firmly rooted in Islamic principles.